1983
DOI: 10.1620/tjem.141.suppl_251
|View full text |Cite
|
Sign up to set email alerts
|

Glucose intolerance in an employed population.

Abstract: Differences in glucose intolerance within various occupational groups , i.e. laborers, clerks, and managers, and the related environmental factors were studied in ca. 9000 male workers of a certain factory. Age-and weight-adjusted prevalence rates of glucose intolerance were 3.2% in the laborers, 5.8% in the clerks, and 9.3% in the managers. In the managers, the total intake of calories was excessive for the amount of exercise expended ; food intake was relatively low in complex carbohy drates and high in anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 8 publications
1
24
0
1
Order By: Relevance
“…Kawachi et al (10) reported an increased prevalence of diabetes in relation to years of nightwork in a cohort study of nurses. In a cross-sectional Japanese study (11) it was observed that diabetes was more common among three-shift workers than among dayshift workers. Another recently published cross-sectional study from Japan did not find differences between shiftworkers and dayworkers (12).…”
Section: Discussionmentioning
confidence: 99%
“…Kawachi et al (10) reported an increased prevalence of diabetes in relation to years of nightwork in a cohort study of nurses. In a cross-sectional Japanese study (11) it was observed that diabetes was more common among three-shift workers than among dayshift workers. Another recently published cross-sectional study from Japan did not find differences between shiftworkers and dayworkers (12).…”
Section: Discussionmentioning
confidence: 99%
“…It was mediated by body weight, while job strain was unrelated to type 2 diabetes risk [26]. Mikuni et al reported a higher prevalence of diabetes mellitus among shift workers [27]. Morikawa et al study suggests that shift work is a risk factor for the onset of diabetes mellitus and that there are different risks associated with different types of shift schedule [28].…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…30,31 These disorders probably occur because sleep plays an important role in the metabolic control of the body. 10,11 Therefore, alterations in the quantity and quality of sleep lead to hormonal disturbances; these might be capable of altering the physiological homeostasis and consequently generate diseases.…”
Section: Anthropometric Evaluationmentioning
confidence: 99%